2020
DOI: 10.3390/met10010085
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Friction Stir Processing on Microstructural, Mechanical, and Corrosion Properties of Al-Si12 Additive Manufactured Components

Abstract: Additive manufacturing (AM) is an advanced manufacturing process that provides the opportunity to build geometrically complex and highly individualized lightweight structures. Despite its many advantages, additively manufactured components suffer from poor surface quality. To locally improve the surface quality and homogenize the microstructure, friction stir processing (FSP) technique was applied on Al-Si12 components produced by selective laser melting (SLM) using two different working media. The effect of F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 16 publications
1
13
0
1
Order By: Relevance
“…Fine segregations of Si-precipitates form inside the saturated Al-matrix. 28,29 The melt tracks are highly visible which was already shown in several studies, 30,31 where the cooling rates differ. In those parabolic sections, a change in size of the AlSi grains results.…”
Section: Microstructuresupporting
confidence: 52%
“…Fine segregations of Si-precipitates form inside the saturated Al-matrix. 28,29 The melt tracks are highly visible which was already shown in several studies, 30,31 where the cooling rates differ. In those parabolic sections, a change in size of the AlSi grains results.…”
Section: Microstructuresupporting
confidence: 52%
“…A few studies already focused on FSP and FSW of additively manufactured aluminum alloys. [ 29–31 ] It was found that an increase in temperature during FSP and FSW, respectively, causes the agglomeration and coarsening of Si‐rich particles deteriorating the strength of the material. Fine Si networks formed in the rapid solidification process play a key role in the strengthening of additively manufactured aluminum alloys.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the feasibility of enhancing the mechanical properties of additively manufactured metals in general and 316 L stainless steel in particular via various SPD methods such as FSP, friction stir welding (FSW), equal channel angular extrusion/pressing (ECAE/P), and high‐pressure torsion (HPT) has attracted attention. [ 28–34 ] During SPD, fragmentation and recrystallization of additively manufactured microstructures led to the formation of ultrafine grained (UFG) materials showing outstanding mechanical behavior. A very recent study showed that FSP has a great potential toward enhancing mechanical properties of additively manufactured 316 L stainless steel as this process could improve tensile strength by 18% with only minimum loss in ductility.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in a recent study by Anas et al [30], corrosion resistance was found to increase with a reduction in crystal size. Similarly, Moeini et al [31] reported enhancement in corrosion resistance in underwater FSP as compared to in-air FSP of additive manufactured Al-Si 12, due to a higher cooling rate that led to a more corrosion-resistant microstructure. The corrosion-protection mechanism may vary between metals and alloys, with finer grains resulting in increasing surface energy, therefore it can be a positive for surfaces that build a passive layer and at the same time a negative [28].…”
Section: Corrosion Behaviormentioning
confidence: 91%